Governança da segurança, ordem social e segurança privada em perspectiva internacional: uma análise do Central City Improvement District da Cidade do Cabo - Marquezi, Marina Biagioni (2023)
Global security governance has undergone significant changes in recent times. Currently, the field of security has been shown to be highly pluralized, since security is not only provided but also governed by different actors inserted in complex networks of interaction. In this scenario, the significant growth of the commercial private security sector stands out. Today private security companies (PSCs) and other actors have become a ubiquitous part of everyday life, given that at least half of the world's population lives in countries where there are more private security officers than police. Several interconnected dynamics, which involve, for example, the diffusion of neoliberal Governance modes, the commodification of security and the diffusion of risk mentalities, resulted in this scenario of pluralization of security governance and expansion of private security. Such processes have even contributed to changing the way of thinking and acting with regards to security, leading to the emergence of new nodes of authority and governance that are simultaneously public, private, local and global in terms of resources, discourses, technologies and actors. These nodes translated, in practice, into new configurations of policing, through which security is carried out based on specific definitions of order, conduct and community. This research turns to understanding the role of private security in the midst of these policing schemes, which have gained considerable relevance both locally and internationally, and what is the ideal of security and order that these services help to reinforce. The case of the Cape Town Central City Improvement District (CCID) is taken as an example to understand the role that private security plays. The project of the Improvement Districts, which became a global reference adopted in many different places, was applied in the capetonian context as a way to guarantee objectives of social order, economic development and urban revitalization. It is argued that, based on these initiatives, private security acts directly to maintain and reinforce distance, inequalities and exclusionary notions of order that, in turn, feed fears and rationales that contribute even more to expanding the demand for its services. This logic is understood as a standard action of PSCs around the world, but it is also worth considering how this is translated through the association with specific local dynamics and produces new modes and practices of governance that spread globally